2021
DOI: 10.7573/dic.2021-7-1
|View full text |Cite
|
Sign up to set email alerts
|

A review of conventional and sustained-release formulations of oral natural micronized progesterone in obstetric indications

Abstract: Background Exogenous progesterone is a treatment option for obstetric indications associated with reduced progesterone activity. Oral natural micronized progesterone (NMP) is effective, although it requires multiple daily doses and may cause adverse events due to its active metabolites. A sustained-release formulation of NMP (NMP-SR) has been developed to overcome the limitations of conventional oral NMP. Methods This narrative review examines the available evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…14 In the present study no side effects like drowsiness, nausea and vomitings were identified with dydrogesterone and sustained release micronized hydroxy-progesterone which was comparable to studies done by Salehpour et al(2013)., 15 and Wagh et al (2021). 16 Similar results were obtained in an RCT done by Herman Tournaye et al and others. 11 In the present study the results obtained proved the use of dydrogesterone for luteal support is beneficial as data depicted in Table 3.…”
Section: Discussionsupporting
confidence: 84%
“…14 In the present study no side effects like drowsiness, nausea and vomitings were identified with dydrogesterone and sustained release micronized hydroxy-progesterone which was comparable to studies done by Salehpour et al(2013)., 15 and Wagh et al (2021). 16 Similar results were obtained in an RCT done by Herman Tournaye et al and others. 11 In the present study the results obtained proved the use of dydrogesterone for luteal support is beneficial as data depicted in Table 3.…”
Section: Discussionsupporting
confidence: 84%
“…Oral progesterone is very convenient for the patients. However, oral medication was previously thought to be ineffective in luteal phase support for ART because of its poor bioavailability, rapid prehepatic and hepatic metabolism, and systemic adverse effects such as somnolence, dizziness, and headache [9]. It is very important to nd an effective, well-tolerated, and easy-to-operate luteal phase support administration.…”
Section: Introductionmentioning
confidence: 99%
“…While in women that are at low risk of preterm birth and with the estimated risk of preterm birth in this population to be 4% (singleton pregnancies, absence of history of preterm birth in previous pregnancy), a correlation appears to exist between preterm birth and cervical length, measured by ultrasound between 19th and 24th week of pregnancy. In these singleton low-risk pregnancies it has been found that a cervical length of 15 mm occupies the third percentile, having a sensitivity of 8.2% and a specificity of 99.7% in the prediction of preterm birth below 32 weeks of gestation, with a cervical length of 25 mm corresponding to the tenth percentile in pregnancies of 16-24 weeks of gestation (threshold below which the cervix is described as "short") [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%